Implementasi Kebijakan dan Sistem Pengendalian Manajemen E-Budgeting dalam mewujudkan Good Governance (Studi Kasus Pada Pemerintah Kota Bandung) - Reviona Juliar; Neneng Dahtiah (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
This study focuses on the application of E-Budgeting in Bandung Municipality as an objective to describe, analyze, and find out the factors that become obstacles to the implementation of E-Budgeting, how the process of E-Budgeting operationalization is and how the effects of policies and management control systems of E-Budgeting in realizing Good Governance is. This research is conducted using qualitative methods, carried out by in-depth interviews with parties or officials who are competent in planning and budgeting. The results show indicate that the variables of bureaucratuc structure, resources, communication, and disposition have gone well. And E-Budgeting management control system that focuses on the implementation of an organizations strategy that has been tunning effectivity and efficiently. The success of the policy of E-Budgeting implementation and its management control system can be proven by the realization of transparency that is carried out in accordance with Undang-undang No. 14 of 2008, accountability in the preparation of the APBD is more accountable and more measurable, and the effectiveness of the APBD that is carried out on time and managed to make efficiency in the budget.